Identifikasi Faktor-Faktor Penyebab Stunting pada Balita di Desa Larangan Tokol Kabupaten Pamekasan - Christiana, Elisa; Reny Eka Darma Saputri; Hilmah Noviandry; Mukhlish Hidayat (Indonesian Health Science Journal, 2025)
Introduction: Stunting is a chronic nutritional problem that has long-term impacts on children's development, both physically and cognitively. Data from the Tlanakan Health Center showed that in August 2023, out of 198 toddlers, 68 toddlers experienced stunting. Objective: to determine the factors that influence stunting in Larangan Tokol Village, Pamekasan Regency. Method: is a type of analytic research with a cross-sectional approach. The samples taken were mothers who had stunted toddlers aged 6-24 months as many as 34 toddlers. The sampling method was purposive sampling. This study uses two variables, namely economy, education, exclusive breastfeeding and knowledge as independent variables and stunting as the dependent variable. Data were analyzed using the chi square test. Results: Education, economic and knowledge factors are closely related to the occurrence of stunting, while exclusive breastfeeding does not affect the occurrence of stunting in toddlers. Conclusion: Education, economic and knowledge factors are closely related to the occurrence of stunting, while providing exclusive breastfeeding has no effect on the occurrence of stunting in toddlers.